2014
DOI: 10.2147/btt.s41477
|View full text |Cite
|
Sign up to set email alerts
|

Update on the use of systemic biologic agents in the treatment of noninfectious uveitis

Abstract: Uveitis is one of the leading causes of blindness worldwide. Noninfectious uveitis may be associated with other systemic conditions, such as human leukocyte antigen B27-related spondyloarthropathies, inflammatory bowel disease, juvenile idiopathic arthritis, Behçet’s disease, and sarcoidosis. Conventional therapy with corticosteroids and immunosuppressive agents (such as methotrexate, azathioprine, mycophenolate mofetil, and cyclosporine) may not be sufficient to control ocular inflammation or prevent non-opht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 127 publications
0
35
0
1
Order By: Relevance
“…18,113,126 In a randomized, multicenter trial on 86 patients, Reinhard et al 125 showed an immune reaction free rate of 89% in the MMF-treated group compared with 67% in the control group during the first year postoperatively. After a mean follow-up of 3 years in the same cohort, Birnbaum et al 19 reported a reaction-free graft survival rate of 83% in the MMF-treated group and 64.5% in the control group.…”
Section: Management Of High-risk Corneal Transplantationmentioning
confidence: 99%
“…18,113,126 In a randomized, multicenter trial on 86 patients, Reinhard et al 125 showed an immune reaction free rate of 89% in the MMF-treated group compared with 67% in the control group during the first year postoperatively. After a mean follow-up of 3 years in the same cohort, Birnbaum et al 19 reported a reaction-free graft survival rate of 83% in the MMF-treated group and 64.5% in the control group.…”
Section: Management Of High-risk Corneal Transplantationmentioning
confidence: 99%
“…2 As uveitis often affects the young adult population in their most productive years of life, the personal and population burden of this sight-threatening disease is noteworthy. 3,4 Conventional therapy with corticosteroids (CS) has been the mainstay to treat uveitis; although CS are often effective, ocular and/or systemic adverse effects limit their long-term use. [5][6][7] Adalimumab (Humira ® ; AbbVie Inc., North Chicago, IL) is a recombinant human immunoglobulin (IgG1) monoclonal antibody that binds specifically to tumor necrosis factor (TNF) and neutralizes its biological function.…”
mentioning
confidence: 99%
“…These agents target molecules in the immune system that play a key role in the ocular inflammatory process(54). For example, TNF alpha, interleukins (IL) and interferons are pro-inflammatory cytokines produced by immune cells and are consistently elevated in serum and aqueous fluid of patients with uveitis(55, 56).…”
Section: Treatmentmentioning
confidence: 99%
“…It is FDA approved for several auto-immune conditions, including rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, plaque psoriasis and inflammatory bowel disease (54). Numerous prospective and retrospective studies support IFX’s use for non-infectious uveitis, but dosage and interval vary (6267).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation